2004
DOI: 10.1163/1568541044038605
|View full text |Cite
|
Sign up to set email alerts
|

Steinernema yirgalemense n. sp. (Rhabditida: Steinernematidae) from Ethiopia

Abstract: Summary -Steinernema yirgalemense, a new species based on morphological and molecular data, is described from Yirgalem, Ethiopia. This nematode belongs to the 'bicornutum-group' which includes nematodes with horn-like structures in the labial region of the infective juvenile. The new species can be recognised by the infective juvenile having a body length of 635 (578-693) µm, distance from anterior and to excretory pore of 51 (45-59) µm; tail length of 62 (57-67) µm and E% (EP/tail length × 100) of 83 (67-90).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…scapterisci is the only tested species known to have a narrow host range and for which a natural host, the mole cricket, has been convincingly demonstrated (38)(39)(40). We found that the olfactory responses of S. scapterisci reflect its host range: S. scapterisci IJs showed the highest virulence to orthopteran hosts and appeared to respond primarily to crickets and cricket-derived odorants (Figs.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…scapterisci is the only tested species known to have a narrow host range and for which a natural host, the mole cricket, has been convincingly demonstrated (38)(39)(40). We found that the olfactory responses of S. scapterisci reflect its host range: S. scapterisci IJs showed the highest virulence to orthopteran hosts and appeared to respond primarily to crickets and cricket-derived odorants (Figs.…”
Section: Discussionmentioning
confidence: 69%
“…H. bacteriophora and S. carpocapsae are thought to have very broad host ranges, with S. carpocapsae capable of infecting more than 250 different species of insects from 13 orders under laboratory conditions (36,37). By contrast, S. scapterisci is an orthopteran specialist with a much narrower host range than most EPNs; its only known natural host is the mole cricket (38)(39)(40). S. glaseri has a somewhat broader host range; it is capable of infecting insects in several orders but is thought to prey primarily on sedentary subterranean larvae, such as those of beetles (36,41,42).…”
Section: H B a C Te Ri O P H O Ra S C A Rp O C A P S A E S S C mentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the versatility of the fruit fly-EPN model system, we compared the ability of symbiont IJs from seven EPN species-S. carpocapsae, S. scapterisci, S. riobrave, S. glaseri, S. feltiae, H. bacteriophora, and H. indica-to infect and kill D. melanogaster larvae. These EPN species differ dramatically in their host ranges: S. carpocapsae and S. feltiae have broad host ranges that include insects from multiple orders, S. scapterisci has a narrow host range that is limited to orthopterans, and the other species have intermediate host ranges (24,(56)(57)(58)(59). S. feltiae was also recently shown to be virulent toward D. melanogaster (3).…”
Section: Resultsmentioning
confidence: 99%
“…Based on laboratory assays, some species infect a broad range of hosts, such as H. bacteriophora and S. carpocapsae (Poinar 1979), while other species have more narrow ranges, such as the S. scapterisci, which is only know to naturally infect mole crickets (Nguyen & Smart, 1990 or S. diaprepsci, isolated from the weevil pest Diaprepes abbreviates L. (Coleoptera: Curculionidae) (Nguyen & Duncan, 2002). A factor which complicates measures of host range is the observation that many EPN species can infect a larger variety of hosts than they would naturally when applied in extremely high numbers (de Doucet, Bertolotti, Giayetto, & Miranda, 1999;Samish & Glazer 1992).…”
Section: Maintaining Reproductive Isolationmentioning
confidence: 99%